River road to China : - Osborne, Milton E. (Archipelago press, 1975)
In 1866, six Frenchmen set out on a dangerous mission to seek a trade route up the Mekong. During the two years that followed, they would journey through more than four thousand miles of unmapped territory, from the tropical heat of the swamps of Vietnam and Cambodia to the bitter cold of the mountain ranges of southwestern China. Their historic expedition is the dramatic subject of River Road to China by world-renowned Southeast Asia expert Milton Osborne. Selected by The New York Times as one of the best books of 1975 when it was originally published, this edition has been updated to include a new postscript by the author and more than thirty full-color illustrations by the expedition's artist.